STUDY OF THE DYNAMIC BEHAVIOR OF THE FRAME BETWEEN THE AXLES IN A VARIABLE-BASE TRACTOR - Artikov Makhmud Sultonboevich (SPAIN- SCIENTIFIC REVIEW OF THE PROBLEMS AND PROSPECTS OF MODERN SCIENCE AND EDUCATION, 2025)
This study focuses on analyzing the structural strength of the main frame in a variable-base tractor design, which serves an important function in cultivating rain-fed sloped lands to help reduce the adverse effects of water scarcity in Uzbekistan’s agricultural sector. The research identifies potential loads and force directions that may arise during field operations, and the impact of these loads on the tractor’s variable-base structure is simulated using SolidWorks software.